2018
DOI: 10.1016/j.rse.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating glacier mass loss on Franz Josef Land, Russian Arctic

Abstract: Franz Josef Land (FJL) in the Russian Arctic, is one of the fastest-warming regions in the Arctic but the glaciers there have not contributed significantly to sea level in the past. We analyze ice surface elevation data derived from satellite stereo imagery (WorldView and SPOT), radar altimetry (CryoSat-2), and a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 46 publications
5
32
0
1
Order By: Relevance
“…We find an interannual variability in the time series of glacier mass change that is similar to that observed on the Svalbard and the Franz Josef Land archipelagoes [7]. In these regions, an increased glacier mass loss between 2010 and 2017 was associated with enhanced ice thinning at the margin of all marine-terminating glaciers [62,86]. This pattern suggests that the NZEM glacier mass balance is largely influenced by shifts in atmospheric and ocean conditions over the entire Barents Sea region.…”
Section: Discussionsupporting
confidence: 70%
“…We find an interannual variability in the time series of glacier mass change that is similar to that observed on the Svalbard and the Franz Josef Land archipelagoes [7]. In these regions, an increased glacier mass loss between 2010 and 2017 was associated with enhanced ice thinning at the margin of all marine-terminating glaciers [62,86]. This pattern suggests that the NZEM glacier mass balance is largely influenced by shifts in atmospheric and ocean conditions over the entire Barents Sea region.…”
Section: Discussionsupporting
confidence: 70%
“…The annual ice volume change and annual ice mass change above sea level are derived from the elevation change, assuming a fixed ice density of 850 ± 60 kg/m 3 (2 sigma; Huss, 2013;Zheng et al, 2018). In order to estimate the ELA, we identify the snow line location from Landsat 8 late-summer images around the entire ice cap and read the corresponding elevations from the DSMs.…”
Section: Methodsmentioning
confidence: 99%
“…To extend the time series, we use SETSM to generate additional WorldView-DSMs from 2017-2019. We use ICESat elevation returns over nonglacierized areas as a standard reference to align all DSMs and calculate DSM uncertainty (Text S1 in the supporting information; Melkonian et al, 2016;Zheng et al, 2018). We mosaic DSMs from March to April each year to (Bassford et al, 2006;Dowdeswell et al, 2002), and elevation difference (j-l).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melkonian et al (2016) [32] reported general ice loss from the glaciers of Novaya Zemlya basing on their newest satellite data analyses. Also, in Franz Josef land glacier retreat is widespread and in general a trend of increasing glacier thinning is observed from the NE towards the SW (Zheng et al 2018) [33]. The process of glacial recession is even more intensive in Svalbard [5,8,19].…”
Section: Discussionmentioning
confidence: 98%